Promoting health in rural Transylvania, Romania. a descriptive analysis of health promotion activities - Baba, Cătălin O; Brînzaniuc, Alexandra; Sirlincan, Emanuela O; Cherecheş, Răzvan M (Central European journal of public health, 2010)
Even though efforts are made to reduce health disparities, promote health for all social groups and improve health outcomes, inconsistencies still exist. Existing evidence shows that lack of funding, lack of properly trained workforce, as well as heavy workload on health care workers, are the most employed explanations for the limited number of health promotion interventions in the area. This paper presents the results of a descriptive study that pursues to render a comprehensive image of health promotion efforts undertaken in rural Transylvania, Romania. This descriptive analysis is conducted on data extracted from a larger dataset, obtained through a study which pursues a cross-sectional design, with a quantitative strategy of inquiry on access to health information in rural Transylvania. The instrument used for data collection is a questionnaire administered by telephone to a sample of medical doctors working in rural medical offices in the studied area (n = 226). Results show overall low rates of health promotion activities in the area, as well as low levels of collaboration with other local actors. In the context of behavioral risk factors, this study clearly shows the need of targeted health promotion activities in rural Transylvania in order to improve health outcomes and mitigate health disparities.
Keywords: Health Promotion; podpora zdraví; Cross-Sectional Studies; Health Behavior; zdraví venkovských oblastí; Public Health Administration; Risk Factors; zdravé chování; Rumunsko; Rural Health; průzkumy a dotazníky; disparity zdravotního stavu; řízení veřejného zdraví; lidé; Humans; Health Status Disparities; rizikové faktory; průřezové studie; Surveys and Questionnaires; Romania